SOSIALISASI KONSEP PARIWISATA BERKELANJUTAN BAGI PENGELOLA DESA WISATA MANGROVE TANJUNG REJO, DELI SERDANG - Sandra Maleachi; Nova Bernedeta Sitorus (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Mangrove Tourism Village of Tanjung Rejo, located in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, offers coastal natural beauty with a sustainable mangrove ecosystem. This village, located just 20 km from Medan City, has the potential to be an ecotourism destination that prioritizes environmental sustainability and the preservation of local culture. Thru sustainable tourism development, this village aims to improve community welfare by creating jobs and increasing income thru the tourism sector. The community service program organized aims to provide socialization about the principles of sustainable tourism and to increase the capacity of the local community in managing tourism destinations. The main focus of this activity includes sustainable destination management, community economic sustainability, cultural preservation and local wisdom, and environmental protection. Thru collaboration between the community, academics, and the government, it is hoped that Mangrove Tourism Village Tanjung Rejo can develop as a destination capable of bringing long-term benefits to the local community, improving the quality of tourism, and promoting nature conservation and local culture. The pre-test and post-test sessions have the same questions. The pre-test was used to assess the understanding of the community in the Mangrove Tourism Village of Tanjung Rejo regarding simple English statements. The post-test was used to determine whether there was an improvement in the residents' understanding after the material was presented. Based on the results of the pre-test and post-test, there was an improvement in the residents' understanding before and after the material was presented, with quite significant results. Based on this, in the future, training like this can be conducted periodically. Keywords: sustainable tourism, Tourist Village, Mangrove